(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article highlights the total transformation and impacts of modern technology in Africa taking into consideration how the youth are embracing the advanced level of computing, the areas where technologies are deplored, the perception an average person has about technology and the predictive results of technology in Africa.